Dose intensification of daunorubicin and cytarabine during treatment of adult acute lymphoblastic leukemia. Issue 1 (28th June 2012) - Stock, Wendy; Johnson, Jeffrey L.; Stone, Richard M.; Kolitz, Jonathan E.; Powell, Bayard L.; Wetzler, Meir; Westervelt, Peter; Marcucci, Guido; DeAngelo, Daniel J.; Vardiman, James W.; McDonnell, Diane; Mrózek, Krzysztof; et al.
Abstract BACKGROUND: Cancer and Leukemia Group B (CALGB) Study 19802, a phase 2 study, evaluated whether dose intensification of daunorubicin and cytarabine could improve disease‐free survival (DFS) in adults with acute lymphoblastic leukemia (ALL) and whether high‐dose systemic and intrathecal methotrexate could replace cranial radiotherapy for central nervous system (CNS) prophylaxis. METHODS: One hundred sixty‐one eligible, previously untreated patients ages 16 to 82 years (median age, 40 years) were enrolled, and 33 (20%) were aged ≥60 years. RESULTS: One hundred twenty‐eight patients (80%) achieved complete remission (CR). Dose intensification of daunorubicin and cytarabine was feasible. At a median follow‐up of 10.4 years for surviving patients, the 5‐year DFS rate was 25% (95% confidence interval, 18%‐33%), and the overall survival (OS) rate was 30% (95% confidence interval, 23%‐37%). Patients aged <60 years who received the 80 mg/m2 dose of daunorubicin had a DFS of 33% (95% confidence interval, 22%‐44%) and an OS of 39% (95% confidence interval, 29%‐49%) at 5 years. Eighty‐four patients (52%) relapsed, including 9 patients (6%) who had isolated CNS relapses. The omission of cranial irradiation did not result in higher than historic CNS relapse rates. CONCLUSIONS: Intensive systemic, oral, and intrathecal methotrexate dosing permitted the omission of CNS irradiation in adult patients with ALL. This intensive approach using higher doses of daunorubicin and cytarabine failed to result in an overall improvement in DFS or OS compared with historic CALGB studies. Future therapeutic strategies for adults with ALL should be tailored to specific age and molecular genetic subsets. Cancer 2013. © 2012 American Cancer Society.